The Correlation Between Vocabulary Mastery and Translation Ability to Students of SMA Negeri 4 Pangkalpinang - Rasuan, Zulfikri B; Fauzi, Fauzi (Berumpun: International Journal of Social, Politics, and Humanities, 2024)
This research focuses on the correlation between vocabulary mastery and translation ability to students of Senior High School (SMA) 4 Pangkalpinang. This study will be conducted by applying a correlational design. It will be used to measure and describe the relationship between two variables in this study namely Independent and Dependent variables. The Independent variable is students’ vocabulary mastery and the dependent variable is the students’ translation ability of the students of SMAN 4 Pangkalpinang. the population of this study were all of the students of grade XI of SMAN 4 Pangkalpinang in academic year 2021/2022. The finding of the research can be concluded that the vocabulary achievement is fair. It can be seen from the computation in which the mean score of the students’ vocabulary achievement is 63.2 when it is consulted to the table of category level scores by John W. Best (2021:260); the score is categorized in fair. the translation ability is fair. It can be seen from the computation in which the mean score of the students’ translation ability is 70.77 when it is consulted to the table of category level scores by John W. Best (2021:260); the score is categorized in fair. There is a significant positive correlation between the vocabulary mastery and translation ability. There is a significant positive correlation between the vocabulary mastery (X) and translation ability (Y).